Struktur Dan Komposisi Vegetasi Pada Berbagai Pola Agroforestri Di Hutan Kemasyarakatan Aik Bual - Muhammad Yul Fikry; Aulia Khairunnisa; Nuzul Rizki Ramadhan (Yayasan Tajuk Indonesia, 2025)
Vegetation structure and composition in various agroforestry patterns in Community Forests (HKm) is one of the common management approaches applied in combining forestry plants with agricultural plants in one area for a sustainable agroforestry system from the environmental and economic aspects of the community. The study aims to analyze the structure and composition of vegetation and its implications for the ecological function and economic value of each pattern. The research method used data collection from 24 observation plots measuring 20m×20m with 38 farmer respondents selected using the stratified random sampling method. Data were analyzed using the Important Value Index (INP), Shannon-Wiener diversity index (H'), Pielou evenness index, and Sørensen community similarity index. The results showed that there were five agroforestry patterns with vegetation structures arranged in five plant strata. The diversity index at the tree level (2.09), pole (1.45), and seedling (1.31) was classified as moderate, while at the sapling level (0.98) was classified as low. The mixed agroforestry pattern (39%) showed the best ecological function, while the dominant durian pattern (16%) with a density index of 31.25 individuals/ha (25.42%) and an Important Value Index (INP) of 50.79% from 14 types of plants in the tree strata and contributed to the highest economic value. The highest INP value of the pole strata was in Durio zibethinus (durian) with an INP of 159.32%, the highest sapling strata was in the Coffea sp. (coffee) type with an INP of 160.14%, and the highest seedling strata was in the Coffea sp. (coffee) type with an INP of 92.02%. This study concluded that the agroforestry system in HKm Aik Bual successfully balanced ecological and economic functions through optimal utilization of vertical space, which has important implications for the development of a sustainable Community Forestry program.